PENGADILAN TINDAK PIDANA KORUPSI DAN TINDAK PIDANA PENCUCIAN UANG - Subihat, Ihat (Yustitia, 2018)
The act of corruption is a violation of every person’s life as stipulated in Article 28A of the 1945 Constitution. As a result of corruption that has been detrimental to the country’s finance or the country’s economy, it also impedes the growth and sustainability of demanding national development high efficiency. For this corruption case, a court for corruption case has been established. Meanwhile, Money Laundering as stipulated in Law No. 8 of 2010 concerning Prevention and Eradication of Money Laundering Crimes, does not have a special court but is often put together with a court of corruption. A court of corruption is the only court that has the authority to examine, hear, and decide the cases of corruption and money laundering crimes whose original crime is a criminal act of corruption; and/or criminal acts which are explicitly stated in other laws as criminal acts of corruption. The problem is how the litigation of corruption and criminal acts of money laundering are incorporated in an indictment of corruption and money laundering. This study used the descriptive method with a normative juridical approach. Data collection was carried out through library studies by collecting data in the form of legal materials; primary, secondary and tertiary legal materials. The analysis technique of this study was descriptive analysis that analyze the process and institutions based on legislation. The results of this study showed that the Corruption Eradication Act regulates materially and formally, so there are exceptions to the principles that are generally regulated in the Criminal Code (KUHP), Criminal Procedure Code (KUHAP) (Lex Specialist Derogate lex Generalis). The modes of money laundering are carried out in various ways. Judging from TPPU modes, it seemed true that TPPU is a stand-alone crime when using cumulative charges is more appropriate. The legal policy of the Corruption Crime Act and Money Laundering Lay (TPPU) related to the rule of law which is the basis of legality for Beneficial Ownership Criminal Liability (BO) as well as its position in Deelneming theory is a topic that must be formulated n the Action Bill Criminal Crime and Money Laundering Crime Bill (TPPU), whether effective evidence for Beneficial Owners (BO), doctrinal or the teaching snares. In the future politics of law enforcement in eradicating corruption and TPPU leads to Beneficial Ownerds (BO) is not enough as long as only the physical actors or stop at the actors revealed in the investigation. Besides the beneficial owner, it is also necessary to regulate criminal liability for legal entities that are used to save the proceeds of money laundering